Cytotoxic and Enzyme Inhibitory Potential of Two Potentilla species (P. speciosa L. and P. reptans Willd.) and Their Chemical Composition - Uysal, Sengul; Zengin, Gokhan; Locatelli, Marcello; Bahadori, Mir B.; Mocan, Andrei; Bellagamba, Giuseppe; De Luca, Elisa; Mollica, Adriano; Aktumsek, Abdurrahman (Frontiers in Pharmacology, 2017)
In this work, the biological and chemical fingerprints of three extracts (ethyl acetate, methanol and water) from two Potentilla species (P. reptans and P. speciosa) were investigated. Antioxidant, enzyme inhibitory, and cytotoxic activities were performed for the biological fingerprint. For the chemical characterization, total bioactive components and individual phenolic components were determined using photometric and HPLC methods, respectively. The main identified phenolic compounds in these extracts were rutin and catechin. Methanol and water extracts contained the highest total phenolic and flavonoid content. The results of antioxidant assays showed that methanol and water extracts displayed higher antioxidant activity compared to the ethyl acetate extract. Generally, methanol and water extracts exhibited higher biological activities correlated with higher levels the bioactive components. For P. speciosa, the methanol extract exhibited the highest enzyme inhibitory activity (except BChE inhibitory activity). P. reptans exhibited also high antiproliferative activity against MCF-7 cells whilst P. speciosa had weak to moderate activity against both of A549 and MCF-7 cell lines. The results suggest that Potentilla species could be potential candidates for developing new phyto-pharmaceuticals and functional ingredients.